Removing all Forms of Soluble Sulphides From Drilling Fluid - Alwan, Hassan A. (Journal of Petroleum Research and Studies, 2016)
The aim of this project is to remove or eliminate the effect of the highly toxic gas of H2S on the health of personal, environment, drilling fluid reology, and drilling equipment materials by adding an economic mixture of sulphide scavengers to the contaminated drilling fluid. In this research mixture of 14.7 gm/l of iron oxide in the form of magnetite (Fe3O4) and 14.7 gm/l of ferrous oxalate Fe(C2O4), which cost is 1.3 US$ per 1kg of mixture, was used to remove the all forms of soluble sulphides (H2S, HS-, S2-) from water-base drilling fluid. The Fe3O4 reacts with dissolved H2S and the reaction carry on fast at pH below 8, while Fe(C2O4) reacts with HS-, S2- and this reaction proceed at high rate at pH above 8. Both reactions produce insoluble iron sulphides. The chemical analysis showed that the soluble species of sulphides in the drilling fluid, which its pH was 7.9, were present as dissolved H2S gas and as bisulphide ions (HS-). The analysis also explained that the total concentration of these sulphides in the drilling fluid was 3000 ppm. The results of treatment of contaminated fluid showed that all forms of sulphides were removed from drilling fluid after adding the mixture of scavengers to the contaminated fluid. The results also explained that the drilling fluid reology recovered after removing the soluble sulphides, which were the main factors that effect on the drilling fluid reology, from the drilling fluid.